2020
DOI: 10.1183/13993003.02096-2020
|View full text |Cite
|
Sign up to set email alerts
|

Low physical functioning and impaired performance of activities of daily life in COVID-19 patients who survived hospitalisation

Abstract: Low physical functioning and impaired performance of activities of daily life in COVID-19 patients who survived the hospitalisation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
246
0
32

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(295 citation statements)
references
References 13 publications
17
246
0
32
Order By: Relevance
“…Our findings are consistent with those of recent studies, 4 , 5 where post-acute COVID-19 patients suffer from dyspnoeaand severe disability. Although information about fatigue is missing in our study; a recent review underlined this as an important outcome in pulmonary rehabilitation.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are consistent with those of recent studies, 4 , 5 where post-acute COVID-19 patients suffer from dyspnoeaand severe disability. Although information about fatigue is missing in our study; a recent review underlined this as an important outcome in pulmonary rehabilitation.…”
supporting
confidence: 94%
“… 3 Two recent studies suggested that early, post-hospitalization rehabilitative interventions would be recommended. 4 , 5 …”
mentioning
confidence: 99%
“… 8 reported that 87% of COVID-19 patients discharged from hospital were still experiencing at least one symptom, and 44% of then had worsened their quality of life. Assessment of functional limitation is needed in COVID-19 survivors to estimate the long-term burden of this illness 9 , 10 . Prospective longitudinal studies measuring objective parameters such as pulmonary function testing, 6-min walk test, quality of life, and detection of depression, anxiety and post-traumatic stress disorder will provide more informative data to understanding of the overall long-term outcomes of SARS-CoV-2 infection.…”
mentioning
confidence: 99%
“… 5 In countries affected early by the pandemic, such as Italy, the need for specific rehabilitation is apparent because of impaired physical function and impaired performance of activities of daily living. 6 …”
Section: Introductionmentioning
confidence: 99%